Becoming the Swan: The Lacanian Mirror Stage and The Illusion of Identity in The Ugly Duckling - Tumiwa, Tessalonika Putri Gracia; Situmorang, Gladys Jessica Sharon; Wijaya, Willy Chandra; Ruata, Sabian Alfaro Petra (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study analyzes Hans Christian Andersen’s The Ugly Duckling through Jacques Lacan’s concept of the mirror stage, highlighting how identity is shaped by external perceptions and societal acceptance. Using psychoanalytic criticism, the research investigates how the duckling’s self-image is formed and transformed through rejection, mockery, and eventual recognition. The findings show that: 1) the duckling initially perceives himself as ugly because of repeated rejection and labeling from those around him; 2) he embarks on a journey in search of acceptance, during which his self-esteem is eroded by constant mockery and social exclusion; and 3) his confidence and self-perception improve only after his physical transformation into a swan, which aligns with societal beauty standards. This study underscores how children’s literature can illuminate the deep psychological impact of social judgment and offers an important reminder to support children in developing positive self-concepts, regardless of appearance.